Modern Competences of the Teacher - Dinara Shamilevna Muminova; Sardorbek G'ulomjonov (Researchparks Publishing, 2022)
Pedagogical experience is the main source of knowledge and accumulated best practices of the best teachers. Historical experience makes it possible to single out something pedagogically valuable from the entire creative heritage of our predecessors, to realize it and consider it as a source of new ideas, goals, content and ways of developing modern education.